Real 3D Geometry and Motion Data as a Basis for Virtual Design and Testing - Weidlich, D.; Zickner, H.; Riedel, T.; Böhm, A. (Cranfield University Press, 2009)
A consistent and accurate digital data model takes a major role during the whole product life cycle of production facilities. This article introduces both technologies: 3D laser scanning for acquisition of 3D geometry date and motion capturing for real motion data with focus on the application in the product life cycle of production facilities. It gives an overview and comparison of different hard- and software solutions. Workflows for concrete tasks in the planning process show how both technologies can be combined and how the acquired data needs to be handled for the integration with CAD tools or Virtual Reality systems. Finally this article gives an outlook on the possible future development of these technologies.
Organised by: Cranfield University
Keywords: Virtual Reality; 3D Laser Scanning; Motion Capture; Ergonomics